2021
DOI: 10.20961/jdc.v5i1.51324
|View full text |Cite
|
Sign up to set email alerts
|

Keteladanan Pengasuh dan Peran Orang Tua dalam Pembentukan Karakter Santri Tarbiyatul Athfal Tegalrejo Magelang

Abstract: Caregivers or kiai in the boarding school have a central role in the process of forming the character of students, but this role cannot run optimally if there is no parental involvement. The purpose of this study was to find out how the role of caregivers and parents in forming the character of Tarbiyatul Athfal students. The method used in this research is qualitative research with a case study research design. The collection technique in this study uses interviews, observation, and documentation. The data ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Keteladanan ini merupakan metode yang paling utama dalam proses pengembangan karakter. Ini karena siswa lebih banyak melakukan peniruan atau imitasi dalam berperilaku (Syarifah et al, 2021). Kedua, metode pembiasaan.…”
Section: Pembahasanunclassified
“…Keteladanan ini merupakan metode yang paling utama dalam proses pengembangan karakter. Ini karena siswa lebih banyak melakukan peniruan atau imitasi dalam berperilaku (Syarifah et al, 2021). Kedua, metode pembiasaan.…”
Section: Pembahasanunclassified
“…Furthermore, Syarifah et al, (2021) conveyed that parental involvement has a vital role in character education because it contributes to the provision of a safe and stable environment, intellectual stimulation, parent-child discussion, a good model of constructive social and educational values and high aspirations related to personal fulfilment and good citizenship. Then Wahyuni & Putra, (2020) revealed that there is cooperation between teachers and parents by being active in every meeting held by the school, fostering children through Islamic education, planting tawhid, holding outing class programs, getting used to praying dhuha, gathering with students' families, activating communication books, being examples of positive habits for daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Maisaro et al (2018) discuss the management of character education strengthening programs at SD Negeri Bunulrejo 2 Malang in collaboration with parents to enhance character education continuously. Next, Syarifah et al, (2021) convey that parental involvement has a vital role in character education because it contributes to the provision of a safe and stable environment, intellectual stimulation, parent-child discussions, good models of social values and constructive education, and high aspirations related to personal fulfillment and good citizenship. Then Wahyuni & Putra, (2020) revealed the existence of collaboration between teachers and parents actively in every meeting held by the school, fostering children by Islamic education, planting monotheism, having outing class programs, getting used to dhuha prayers, getting together with students' families, activating communication books, becoming examples of habits -positive habits for daily activities.…”
Section: Introductionmentioning
confidence: 99%